Efektifitas Penggunaan Kompres Metronidazol dan NaCl 0,9% terhadap Penyembuhan Luka Diabetik di RSUD Margono Soekarjo Purwokerto - Supriyatin; Saryono; Latifah, Lutfatul (Jurusan Keperawatan FIKES UNSOED, 2007)
Diabetic wound needs continous nursing intervention, therefore healing process can effectively achieved There are some solutions used to care diabetic wound such as NaCL 0.9%, metronidazole, bee honey however until now there is no study shows effectiveness of those solutions. This study aims to compare effectiveness of Metronidazole and NaCL 0.9% to diabetic wound healing which include its wound dimension, odor, secretion, and granulation growth. This comparative study used Qusi Experimental Method and Non Ã‚Â¬Equivalent Control Group Design. Population was patiens cared in Kenanga and Teratai (Surgical Medical Ward) In-patient Department, Margono Soekarjo General Hospital Purwokerto. This study recruited 20 people as sample from July to September 2006 based on order of admission, odd numbers, were given metronidazole compress and even numbers were given NaCL 0.9% compress on their wound management. Prior to statistical test, data had been comprehensively tested and had fulfilled normal distribution requirements with Leveń test then \